Assessment of lingual sentinel lymph nodes metastases using dual-modal indirect CT/MR lymphography with gold–gadolinium-based nanoprobes in a tongue VX2 carcinoma model. (3rd August 2018) - Yang, Yue; Zhou, Benqing; Zhou, Jian; Shi, Xiangyang; Sha, Yan; Wu, Haitao
Abstract: Objective: To evaluate the capability of indirect computed tomography and magnetic resonance lymphography (CT/MR-LG) with gadolinium-loaded, polyethylenimine-entrapped gold nanoprobes (Gd-Au PENPs) for assessing lingual sentinel lymph node (SLN) metastasis in a tongue VX2 carcinoma model. Materials and methods: Seventeen rabbits were used to establish a metastatic cervical lymph node model by implanting VX2 carcinoma suspension into the ventral tongue muscle. CT and MR images were acquired one hour after Gd-Au PENPs injection into the tongue submucosa bilaterally, on 1w ( n  = 4), 2w ( n  = 6) and 3w ( n  = 7) tumour-bearing rabbits after carcinoma transplantation. Then, the filling defects and enhancement features of the lingual SLN on indirect CT/MR-LG were assessed. Results: The enhanced lingual SLNs were observed bilaterally in all rabbits using indirect CT/MR-LG. In total, 15 enhanced SLNs displayed oval or round shape with uniform density and no filling defects or only local small filling defects, and all nodes were metastasis-negative, while 19 enhanced SLNs demonstrated irregular morphologies with filling defects, non-uniform densities and unclear borders, of which 14 nodes were metastatic. The sensitivity, specificity, accuracy, positive predictive value and negative predictive value when using SLN enhancement with irregular morphology, filling defects, non-uniform density and unclear border as diagnostic criteria for metastasis were 100%, 75.0%, 85.3%, 73.7% and 100%, respectively. Conclusions: Indirect CT/MR-LG with Gd-Au PENPs can be used for the metastatic diagnosis of lingual SLN in tongue cancer.